The Effect of Team Diversity on R&D Licensing in the Thai Public Research Institute - Warangkana Punyakornwong (STI Policy and Management Journal, 2018)
The main objective of this study is to examine the effect of team diversity and institutional factors in terms of top management support and incentive system on the number of license agreements in the context of the National Science and Technology Development Agency (NSTDA) in Thailand. The sample size is NSTDA’s licensed and unlicensed projects in between 2011 and 2015. Data has been collected through a survey carried out on a sample of 134 licensed projects drawn from the population of 144 licensed projects between 2011 and 2015. With limitation of time and sensitivity of identifying about unsuccessful projects, only 29 unsuccessful projects were identified. Consequently, the total projects to be examined by Poisson regression analysis were 163 projects. The results of the identification of the research teams in each licensed project indicated, a statistically significant positive relationship between the high degree of difference in terms of educational major/fields, the high degree of differences in experience and the number of license agreements. It contributes to a cognitive resource theory which suggests that diversity facilitates a more complex problem-solving process. In addition to team diversity, top management support as the institutional factor, is also another key success factor in supporting effective research team to enhance the number of license agreements. Keywords: team diversity, Public Research Institutes (PRIs), licensing, top management support